Implementing Fault-Tolerant Distributed Systems with Azure Service Fabric and .NET Core - Sai Vaibhav Medavarapu (North American Journal of Engineering Research, 2023)
Fault tolerance is critical in distributed systems to ensure high availability and reliability. Azure Service Fabric, combined with .NET Core, provides a robust platform for developing fault-tolerant distributed applications. This paper explores the implementation of such systems, highlighting the architecture, design patterns, and practical aspects of deploying fault-tolerant services using these technologies. Through a series of experiments, we demonstrate the effectiveness of various fault- tolerance strategies and provide insights into their performance implicatio